MANAJEMEN WAKAF TANAH MASJID AL HIKMAH PADA DESA KECILA KECAMATAN KEMRANJEN (Studi Pada Wakaf Sumur Bor) - Siti Maliah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Waqf in practice, in Indonesia as often found in the form of buildings such as mosques, prayer rooms, schools, and other social buildings constructed for public servants. The type of research used in this study is a qualitative field research (research field).The technique used in this research data collection is to use observation, interview, and documentation. Data analysis used includes data reduction, data presentation, and draw conclusions. Based on data analysis that has been carried out by researchers, it has resulted in a conclusion that the management of waqf land at the Al Hikmah Mosque has so far been good in implementing management functions in the form of (planning, organizing, implementing and supervising) in achieving the goal of producing productive waqf wells. drill. Management of the Al Hikmah Mosque land waqf in the drilled well waqf in Kecila Village, Kemranjen District, which was only created in January and completed in March 2024 with funding assistance from BI (Bank Indonesia) amounting to IDR 108,400,000 and began operating in May 2024 with a total of 13 customers with results of Rp. 106,000.